PENGARUH KEPEMIMPINAN PELAYAN DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA KARYAWAN JASA PENGIRIMAN - Lukas Purwoto; Alfonsus Widiarto; Christina Heti Tri Rahmawati (Universitas Sarjanawiyata Tamansiswa, 2023)
This study gives primary attention to the behavior of leaders in an effort to improve employee performance. The research objective was to examine the effect of servant leadership and interpersonal communication on employee performance. The research was conducted by taking respondents from employees who were working in a delivery service organization. The data collection method was carried out by distributing questionnaires to respondents in a sample that took all members of the population. Data analysis was carried out by applying multiple regression which was assisted by processing it with a computer program. The research results show that servant leadership and interpersonal communication are important attributes of service delivery organization managers when managing employees towards high performance.